Czy Joanna Chmielewska pisała kryminały? = Did Joanna Chmielewska write detective novels? - Gazdecka, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The essay aims to place the work of Joanna Chmielewska within the framework of existing literary genres. Simultaneously, it attempts to characterize the features of "ironic crime novel" - the novel type created by Chmielewska. The paper discusses briefly the reasons behind the wide appeal of the books with Joanna as their protagonist. The author also focuses on the reasons behind the popularity of Chmielewska's crime novels, analyzing them as a cultural phenomenon.
Keywords: Chmielewska, Joanna (1932-2013); literatura polska - 20 w. - tematyka; powieść kryminalna